(untitled) (Medicina y Seguridad del Trabajo, 2022)
Introduction: Cardiovascular disease is currently one of the most prevalent non-communicable diseases, affecting nearly 57% of the world’s population, accounting for 32% of deaths worldwide. The aim of the study is to determine the cardiovascular risk of teaching staff. Methods: Retrospective, cross-sectional study carried out on 4,738 teachers from different Spanish geographical areas with a mean age of 41 years. Different variables related to cardiovascular risk are determined, such as overweight and obesity scales, nonalcoholic fatty liver scales, atherogenic indices, metabolic syndrome and cardiovascular risk scales, among others. Results: Among the results we highlight a prevalence of hypercholesterolemia of 41%, hyperteriglyceridemia 12.1%, hypertension 15.5%, obesity using BMI 13%, high risk of fatty liver 11.3% and moderate or high SCORE values 11.4%. Conclusion: The teaching staff is not free from developing CVD that we can relate to the lack of physical activity and an unhealthy diet that increases the prevalence of obesity and overweight.